Kepemimpinan Multikultural Transformasional: Navigasi Nilai Sunatullah dan Moderasi Beragama bagi Gen Z di Ruang Digital - Muhammad Nur Romdloni; Mufidatul Munawaroh (AJER: Advanced Journal of Education and Religion, 2026)
This research explores the urgency of Transformational Multicultural Leadership as a value navigation instrument amidst the complexities of digital disruption affecting Generation Z in Indonesia. In an era where social media algorithms frequently create echo chambers and identity polarization, Gen Z is confronted with a paradox of value disorientation and a crisis of multiculturalism. Using a qualitative method through library research, this study performs a critical synthesis of modern transformational leadership theory with Islamic theological foundations, namely the values of Sunatullah (the natural law of diversity) and Religious Moderation (Wasathiyah). The research results indicate that transformational leadership in the digital sphere must shift from hierarchical authority to networked influence that prioritizes authenticity and intellectual stimulation. The navigation of Sunatullah values serves to provide an ontological basis that plurality is an absolute divine decree, while Religious Moderation acts as an operational strategy—encompassing national commitment, active tolerance, and anti-violence—to shield Gen Z from the pull of radical extremism and secular liberalism. These findings formulate an integrative digital leadership framework that positions Gen Z not merely as content consumers, but as subjects of change (micro-influencers) capable of internalizing moderation as a sustainable digital lifestyle to maintain social cohesion and national stability in the future.